2020
DOI: 10.1073/pnas.2011780117
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived organoid retinoblastoma reveals a cancerous origin

Abstract: Retinoblastoma (Rb) is the most prevalent intraocular malignancy in children, with a worldwide survival rate <30%. We have developed a cancerous model of Rb in retinal organoids derived from genetically engineered human embryonic stem cells (hESCs) with a biallelic mutagenesis of the RB1 gene. These organoid Rbs exhibit properties highly consistent with Rb tumorigenesis, transcriptome, and genome-wide methylation. Single-cell sequencing analysis suggests that Rb originated from ARR3-positive maturing cone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 50 publications
7
76
0
Order By: Relevance
“…In parallel, pluripotent stem cell derived organoid retinoblastoma models have recently been generated, corroborating the Arrestin 3 + maturing cone precursors as cell of origin for Rb. 14 Next-generation sequencing methods have enabled detection of mutations in peripheral blood samples at a low level of mosaicism that would have been missed with the traditional sequencing methods. Notwithstanding, it has not been possible to assess the full spectrum of clonal types within the tumor or the molecular changes occurring at the cells of origin, which are likely to be characterized by a different transcriptional and epigenetic profile.…”
mentioning
confidence: 99%
“…In parallel, pluripotent stem cell derived organoid retinoblastoma models have recently been generated, corroborating the Arrestin 3 + maturing cone precursors as cell of origin for Rb. 14 Next-generation sequencing methods have enabled detection of mutations in peripheral blood samples at a low level of mosaicism that would have been missed with the traditional sequencing methods. Notwithstanding, it has not been possible to assess the full spectrum of clonal types within the tumor or the molecular changes occurring at the cells of origin, which are likely to be characterized by a different transcriptional and epigenetic profile.…”
mentioning
confidence: 99%
“…Single cell transcriptome profiling of tumors and developing tissues has proven to be a promising tool to reveal such processes, which could potentially serve as therapeutic targets (Filbin et al, 2018;Zhang et al, 2019). Similar methods can also be applied to in vitro models recapitulating embryonal tumorigenesis, as demonstrated for the retinoblastoma organoid model generated by Liu H. et al (2020), which has the advantage that it allows for a direct comparison of normal and tumor development. Although many in vitro embryonic cell-derived tumor models have been established over the years, the spectrum is biased toward ectoderm-derived tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transplantation of RB1-null organoids into immune-deficient mice did not result in retinoblastoma formation (Zheng et al, 2020). In contrast, Liu H. et al (2020) utilized an alternative hESC-derived retinal organoid model, in which RB1 depletion did successfully generate tumors upon xenografting and better resembled patient retinoblastoma. These findings illustrate that the finetuning of retinal organoid establishment can affect the outcome of RB1 depletion, possibly due to differences in cellular composition and the presence or absence of the cell-of-origin.…”
Section: Pluripotent Stem Cell-derived Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators further assessed the possible mechanism of this circRNA through RPE cell lines and found that circNR3C1 protected RPE functions via the circNR3C1-miR-382-5p-PTEN network ( Figure 4B). Retinoblastoma (Rb) is an important cause of blindness in early childhood (Liu et al, 2020). CircRNAs have also been shown to be dysregulated in RB and some RB cell lines.…”
Section: Retinal Diseasementioning
confidence: 99%